Highly sensitive and stretchable piezoresistive strain sensor based on conductive poly(styrene-butadiene-styrene)/few layer graphene composite fiber. (February 2018) - Wang, Xingping; Meng, Si; Tebyetekerwa, Mike; Li, Yilong; Pionteck, Jürgen; Sun, Bin; Qin, Zongyi; Zhu, Meifang
Abstract: High stretchability and sensitivity are the major desired requirements of strain sensors for wearable electronics applications, especially in health and medical monitoring. Herein, a highly sensitive and stretchable strain sensor based on conductive poly(styrene-butadienestyrene)/few layer graphene (SBS/FLG) composite fiber is fabricated through an easy and scalable wet-spinning process. Owing to the super flexibility of SBS matrix and the excellent electrical and mechanical properties of FLG, the SBS/FLG fiber based strain sensor revealed superior performance, including wide workable strain range (>110%), superior sensitivity (gauge factor of 160 at a strain of 50% and of 2546 at a strain of 100%), and durability. Furthermore, the mechanism behind the excellent performances of SBS/FLG fiber based sensors is discussed in detail.